Peran Kepala Sekolah dalam Implementasi Kurikulum Merdeka di Taman Kanak-Kanak - Siti Atikatul Hasanah; Kurniah Astutik (CV. Lentera Literasi Indonesia, 2026)
The implementation of the Merdeka Curriculum in early childhood education requires the role of school principals who are able to support flexible, creative, and child-centered learning processes. However, several challenges are still found in its implementation, such as teachers’ readiness to face curriculum changes and the use of learning technology. This study aims to describe the role of the principal in implementing the Merdeka Curriculum at TK Nurur Rahman Tamanan. This research used a qualitative approach with a descriptive qualitative design. The research data sources were obtained from the principal and teachers of TK Nurur Rahman Tamanan. Data collection techniques were conducted through interviews, observations, and documentation. The results showed that the principal played roles as a mentor, motivator, supervisor, and agent of change in implementing the Merdeka Curriculum. The principal provided support to teachers through training programs, learning communities, webinars, and learning coordination to improve teachers’ competencies in implementing play-based learning and the use of creative learning media. In addition, the implementation of the Merdeka Curriculum also had a positive impact on children’s development, such as improving creativity, independence, and confidence in learning. Therefore, the successful implementation of the Merdeka Curriculum in kindergarten is influenced by adaptive, collaborative, and supportive school leadership in developing teacher competenci